VOLTAMMETRIC ELECTROCATALYTIC OXIDATION OF ASCORBIC ACID ON ?- NICKEL HYDROXIDE NANOPARTICLES MODIFIED CARBON PASTE ELECTRODE - Hidayat, Fathoni
Ascorbic acid (AA), or Vitamin C, is an antioxidant that can prevent oxidation-triggering reactions that can to lead cell damage. Vitamin C is also required for biosynthesis in human body. Humans cannot self-produce AA, they need it to intake from their food such as fruits, vegetables and supplements. Therefore, a sensitive and accurate AA method for AA determination in food products is needed. The voltammetry method has been widely developed for AA analysis because it has several advantages, such as easy sample preparation, easy measurement process, low analysis costs, and high sensitivity and selectivity. In this study, we modified carbon paste electrode (CPE) with ?-nickel hydroxide (?-Ni(OH)2) nanoparticles to electrocatalytically oxidized AA. The ?-Ni(OH)2 nanoparticles can accelerate electron transfer during AA oxidation which increase the sensitivity of the analysis. In this study, ?-Ni(OH)2 nanoparticles was synthesized using two different methods, namely the hydrothermal method at 170 °C for 24 hours using an autoclave set, and the sonochemical method at 55 °C for 1 hour. The synthesized products were characterized using FTIR and XRD. The characterization results showed the presence of Ni-O and O-H groups in the producs of both methods. The products of both methods have ? phase with an average particle diameter of 76.85 nm for the hydrothermal method, and 42.96 nm for that of sonochemical method which proved that the products are ?-Ni(OH)2 nanoparticles. The performance of CPE modified with ?-Ni(OH)2 nanoparticles (CPE-Ni) characterized using cyclic voltammetry (CV) technique showed that AA oxidation peak appeared at potential of 0.24 V vs Ag/AgCl (3 M). This oxidation peak was 0.125 V more negative than that obtained with unmodified CPE showing an electrocatalytic process. The optimum composition of the modifier, based on the peak width of the cyclic voltammogram was 2% (w/w), meanwhile based on the baseline stability and symmetrical voltammogram was 10% (w/w). Furthermore, literature studies for optimim measurements pH using CPE-Ni depended on the analytes. In general, the optimum pH for voltammetric electrocatalytic oxidation of AA was 7, with phosphate buffer as supporting electrolyte. Based on literature studies on the performance of electrodes modified with ?- Ni(OH)2 nanoparticles, it can be concluded that this modified electrodes have excellent measurement sensitivity and selectivity and are stable for repeated measurements.